ANALISIS PENGARUH FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, PENDIDIKAN ORANG TUA DAN PARENTAL INCOME TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA MAHASISWA S1 UNIVERSITAS ANDALAS PADANG - Fadilla Khairani, Mohamad Fany Alfarisi (Departemen Manajemen, 2019)
This research aims to determine the effect of influence financial attitudes, financial knowledge, parental education and parental income to financial management behavior to students in Andalas University. This research using convenience sampling technique whichis done to 378 samples. The methods used questionnaire and interviews. The data was design as a questionnaire based and analyzed by using SPSS. The results of research indicate that the financial attitude had significant positive correlation, the financial knowledge had not significant correlation, the parental education and parental income had significant negative correlation with financial management behavior to students in Andalas University. The implications is the students can make financial planning in order to train more responsible financial behavior, and beside that students also need to realised that ability to act and make decisions in finance is very important to manage finances better.